Vikings, peat and settlement abandonment : a multi-method chronological approach from Shetland. - Swindles, G.T.; Outram, Z.; Batt, C.M.; Hamilton, W.D.; Church, M.J.; Bond, J.M.; Watson, E.J.; Cook, G.T.; Sim, T.G.; Newton, A.J.; Dugmore, A.J. (Quaternary Science Reviews, 2019)
Understanding the chronology of Norse settlement is crucial for deciphering the archaeology of many sites across the North Atlantic region and developing a timeline of human-environment interactions. There is ambiguity in the chronology of settlements in areas such as the Northern Isles of Scotland, arising from the lack of published sites that have been scientifically dated, the presence of plateaus in the radiocarbon calibration curve, and the use of inappropriate samples for dating. This novel study uses four absolute dating techniques (AMS radiocarbon, tephrochronology, spheroidal carbonaceous particles and archaeomagnetism) to date a Norse house (the “Upper House”), Underhoull, Unst, Shetland Isles and to interpret the chronology of settlement and peat which envelops the site. Dates were produced from hearths, activity surfaces within the structure, and peat accumulations adjacent to and above the structure. Stratigraphic evidence was used to assess sequences of dates within a Bayesian framework, constraining the chronology for the site as well as providing modelled estimates for key events in its life, namely the use, modification and abandonment of the settlement. The majority of the absolute dating methods produced consistent and coherent datasets. The overall results show that occupation at the site was not a short, single phase, as suggested initially from the excavated remains, but instead a settlement that continued throughout the Norse period. The occupants of the site built the longhouse in a location adjacent to an active peatland, and continued to live there despite the encroachment of peat onto its margins. We estimate that the Underhoull longhouse was constructed in the period cal. AD 805–1050 (95% probability), and most probably in cal. AD 880–1000 (68% probability). Activity within the house ceased in the period cal. AD 1230–1495 (95% probability), and most probably in cal. AD 1260–1380 (68% probability). The Upper House at Underhoull provides important context to the expansion and abandonment of Norse settlement across the wider North Atlantic region.